Type specimens of birds of the genus Batis (Aves: Platysteiridae) at the Museum für Naturkunde Berlin - Frahnert, Sylke; Louette, Michel; Eckhoff, Pascal (Zootaxa, 2021)
The ornithological collection of the Museum für Naturkunde Berlin houses an important collection of birds of the genus Batis, with many type specimens used in descriptions dating from the 19th and beginning of the 20th century. Some of these scientific names are still in use today, but others are synonyms. We herein provide an updated list of all this type material for 10 names (species and subspecies) with 34 types and 21 paratypes, and we designate a lectotype for Batis puella Reichenow, 1893.